Moving from theory to practice: experience of implementing a learning supporting model designed to increase patient involvement and autonomy in care - Svanström, Rune (BMC Res Notes, 2016)
BACKGROUND: In implementing new programs of care, such as person-centered care, there is a risk that the focus will be at an organizational level, instead of a level that describes what happens in the personal development among staff. The aim of this study was to describe experiences of the implementation process of a learning supporting model designed to increase patient involvement and autonomy in care. The project, which lasted 2 years, involved training sessions, supervision and reflective meetings. Over the period, the staff who participated focused on developing their dialogues with patients to make the patients aware of their own capabilities and to encourage them to be fully involved in the treatment. A reflective lifeworld approach was used. Data were collected through interviews, notes and written stories, and analyzed using hermeneutic analysis with a focus on meanings. RESULTS: At the beginning of the project, the participants perceived the model as abstract and difficult to understand but supervision and reflection sessions enabled understanding and changed the participants’ approach to caring. The participants described the model as an approach used in challenging patients to become involved in their care and to take charge of their lives when living with a chronic life-threatening disease. The participants’ experience of implementing the model has not been easy but has led to increased self-confidence and feelings of improved competence in dialogue with patients. CONCLUSIONS: Using the PARISH model when critically examining the results shows that in the implementation process there were some difficulties, e.g. the context was supportive and facilitating but there was no appointed facilitator. By making participation in improvement work voluntary, the impact of such work becomes less efficient, less cost-effective and probably less sustainable. Furthermore, implementation needs encouragement since changing approaches takes time and requires patience. Group supervision sessions seem an appropriate way to translate research into practice; systematic scheduled and mandatory group supervision sessions would, therefore, probably make implementation more robust and sustainable. In addition, a well-trained facilitator would be able to motivate staff to undertake daily reflection and participate in group supervision sessions. Reflection seems to be a key component in the personal learning necessary to change work routines and approaches.